2018
DOI: 10.1186/s12931-018-0861-5
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta1 targets estrogen receptor signaling in bronchial epithelial cells

Abstract: BackgroundSex differences in idiopathic pulmonary fibrosis (IPF) suggest a protective role for estrogen (E2); however, mechanistic studies in animal models have produced mixed results. Reports using cell lines have investigated molecular interactions between transforming growth factor beta1 (TGF-β1) and estrogen receptor (ESR) pathways in breast, prostate, and skin cells, but no such interactions have been described in human lung cells. To address this gap in the literature, we investigated a role for E2 in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 94 publications
1
21
1
Order By: Relevance
“…70 The activation of the ERs can modulate pro-inflammatory cytokines due to inhibition of NF-κB, an important nuclear factor for cellular signaling, limiting the severity of the inflammation. 71,72 In ARDS, one of the severe complications of COVID-19, experimental studies have suggested a protective role of estrogen. Rats submitted to acute lung injury induced by seawater aspiration have pulmonary edema reductions by downregulation of aquaporins after the administration of 17β-estradiol.…”
Section: Estrogen Role In Lung Inflammationmentioning
confidence: 99%
“…70 The activation of the ERs can modulate pro-inflammatory cytokines due to inhibition of NF-κB, an important nuclear factor for cellular signaling, limiting the severity of the inflammation. 71,72 In ARDS, one of the severe complications of COVID-19, experimental studies have suggested a protective role of estrogen. Rats submitted to acute lung injury induced by seawater aspiration have pulmonary edema reductions by downregulation of aquaporins after the administration of 17β-estradiol.…”
Section: Estrogen Role In Lung Inflammationmentioning
confidence: 99%
“…100 On the other hand, a recent study reported that transforming growth factor beta1 (TGF-b1) represses the expression of ERa in bronchial epithelial cells. 65 There are two classes of ERs: the nuclear ERs: ERa (ESR1) and ERb (ESR2), and the membrane ERs: mERs (G protein-coupled ER 1, GPER/GPER30). 101 Estrogen directly binds to the nuclear ERs, triggering receptor dimerization and binding to estrogen response elements (EREs) in the promoter region of target genes.…”
Section: Estrogenmentioning
confidence: 99%
“…[6] In bronchial epithelial cells, estrogen and transforming growth factor beta1 have been shown to inversely modulate the expression of several genes involved in extracellular matrix turnover, airway smooth muscle cell contraction, and calcium flux regulation. [7] Adipose tissue accounts for the majority of peripheral estrogen synthesis and its contribution to the circulating pool of estrogens increases with body mass and age. [17] It has been shown that bariatric surgery in women can lead to significant decreases in estradiol, total testosterone, and dehydroepiandrosterone sulfate (DHEA-S) as well as significant increases in follicle stimulating hormone, luteinizing hormone, and sex hormone binding globulin.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity can be both a consequence of sarcoidosis treatment and a contributor to disease risk likely through the pro-inflammatory environment of obesity. [5] Although the etiology of sarcoidosis progression is still largely unknown, recent studies propose a role for sex hormones [6][7][8][9] and the microbiome in the pathogenesis of fibrotic lung disease. [10][11][12] These gaps in knowledge limit the identification of effective treatments.…”
Section: Introductionmentioning
confidence: 99%